Pharmacist-led interventions in brazil: A scoping review protocol - Lucchetta, Rosa Camila [UNESP]; Forgerini, Marcela [UNESP]; Mastroianni, Patricia de Carvalho [UNESP] (My University, 2018)
Drug-related problems consist an important avoidable risk factor to the hospitalization in the general population. The increase of technologies to promote and recovery health and their use makes the design of services aimed at preventing health and drug problems, as well as their adequate management, a priority for public health. Pharmacist-led interventions are capable to optimize the use of medicines. However, it is important to know the characteristics and assessed outcomes of interventions, since, as a complex intervention, the variability between services can explain different performances. The objective of the scoping review is to explore randomized and non-randomized clinical trial, quasi-experimental and cohort studies to explore characteristics and assessed outcome of pharmacist-led interventions conducted in Brazil. This review will consider studies about pharmacist-led interventions, regardless of patient profile or health setting. Electronic searches will be performed in PubMed, Scopus, and LILACS databases with no time limit of publication. Two researchers, independently, will select registries and extract data of study and service characteristics, and outcomes measures. The findings will be presented in a narrative form including tables and figures to aid in data presentation, where appropriate.
Intervenções farmacêuticas no brasil: Um protocolo de revisão de escopo
Keywords: Community Pharmacy Services; Medication Therapy Management; Patient Care; Patient Safety; Pharmaceutical Services